LEGAL FORCE OF ILLEGAL ONLINE LENDING AGREEMENTS AND CONSUMER PROTECTION IN INDONESIA (International Journal of Cultural and Social Science, 2026)
This study analyzes the legal validity and binding force of agreements in illegal online lending services and their implications for consumer protection in Indonesia. The rapid growth of fintech lending has increased the prevalence of illegal providers that operate outside the supervision of the Financial Services Authority (OJK). This research employs a normative juridical method using statutory and conceptual approaches. The study examines the Indonesian Civil Code, consumer protection regulations, and relevant financial service regulations. The findings show that agreements in illegal online lending services do not fulfill the lawful cause requirement under Article 1320 of the Indonesian Civil Code and may also involve defects of consent, rendering them legally defective or void. In addition, prohibited standard clauses weaken the binding force of such agreements against consumers. The study concludes that stronger regulatory enforcement and consumer protection mechanisms are necessary to ensure legal certainty in digital financial transactions.